Causes of Non-fulfillment of Article 1 of the Underage Marriage Law - Ferawati Lasimpala (Estudiante Law Journal, 2026)
The purpose of this research is to find out and analyze the factors causing the non-fulfillment of Article 1 of the Marriage Law on underage marriages. Types of normative-empirical legal research. Normative-empirical legal research (applied law research) is research that uses normative-empirical legal case studies in the form of legal behavior products. The type of data used in this research is secondary data but does not rule out the possibility of conducting field research by examining primary data. The position of Article 1 of Law Number 1 Year 1974 Concerning Marriage in Batudaa District, namely, the purpose of marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming an eternally happy family (household) based on Belief in Almighty God. It has not materialized properly due to household problems that ended in divorce, while household problems can be underlined as; 1, poor communication relations, 2, unfavorable rights and obligations of husband and wife, 3, interference from parents or in-laws.